Real-world effectiveness of mepolizumab in Japanese asthma patients with diverse backgrounds: Improvements in rhinosinusitis imaging (J-Real-Mepo) - Hiroyuki Nagase; Konomi Kobayashi; Makiko Toma-Hirano; Maho Suzukawa; Norihiro Harada; Katsunori Masaki; Yoshito Miyata; Mayoko Tsuji; Junko Terada-Hirashima; Keiko Komatsuzaki; Hitoshi Sasano; Kenji Mizumura; et al. (Allergology International)
Background: Although randomized controlled trials (RCT) have demonstrated the efficacy of mepolizumab for asthma, they have excluded certain patient subgroups. To bridge the gap between RCT and real-world practice, the effectiveness of mepolizumab in a diverse population, including those potentially excluded from RCT, was assessed. Its effects on imaging findings and symptoms of chronic rhinosinusitis (CRS) with asthma were also assessed. Methods: This retrospective observational study of patients in Japan (J-Real-Mepo: UMIN000045021) evaluated multiple endpoints and analyzed the relationship between clinical background and treatment outcomes. Results: Mepolizumab significantly reduced exacerbations, improved Asthma Control Test (ACT) scores, and forced expiratory volume in 1 s, and reduced oral corticosteroid (OCS) dose, regardless of patient characteristics, including age, body mass index, smoking history, and comorbidities. Regarding RCT exclusion criteria, 29.4 % of patients had no history of exacerbations. Although 25.4 % of these patients required continuous OCS, the OCS dose was reduced similar to those with a history of exacerbations. Disease control and mepolizumab effectiveness in patients with a smoking history ≥10 pack-years was similar to that of never-smokers. Patients with eosinophil counts <150/μL had lower ACT scores and higher OCS use compared with patients with eosinophilia and comparable effectiveness regarding exacerbation and OCS reduction. Significant improvements in Lund–Mackay scores and CRS symptoms were observed. Conclusions: Mepolizumab effectiveness was demonstrated in a broad range of patients including those with RCT exclusion criteria, who had significant disease or OCS burden. These findings may explain the consistent results between RCT and real-world studies of mepolizumab.